Empirical Evidence of Asset Pricing Based on Single Index Model, Fama, and French Three and Five-Factor Models in Indonesia Stock Exchange - Silvia, Ani; Griska, Chikita Tiara (Akurasi : Jurnal Studi Akuntansi dan Keuangan, 2021)
This empirical test aims to estimate the beta parameters of the risk premium and other risk factors and compare the performance of the single-index model, Fama and Frech three and five-factor models. The sample used as the study object is companies in the property and real estate subsector with data collected from datastream Thomson Reuters from January 2014 to December 2018. The results are consistent with the previous studies that asset pricing using the Fama and French five-factor model can better explain stock returns than the other two models. The property and real estate subsector seems to provide a positive and statistically significant abnormal return, indicating that asset pricing with the three models is irrelevant to Indonesia. These results suggest that the stock market in Indonesia is still inefficient.